Potensi Ekonomi Mina Padi di Kedah Malaysia dan di Indonesia - Apriyani, Anita; Siregar, Sasmita; Rahim, Hairazi; Putra, Yudha Andriansyah (JURNAL AGROPLASMA, 2024)
Government agricultural policies around the world prioritize increasing domestic production, productivity and sustainability while addressing food security and resource constraints. One promising strategy that is gaining global attention is integrating rice and fish cultivation. This approach offers ecological and economic benefits, such as increased soil fertility, natural pest control, and increased household income. This approach offers ecological and economic benefits, such as increased soil fertility, natural pest control, and increased household income.Integrated aquaculture is an efficient method for overcoming scarcity of food and land resources. This research aims to analyze the economic potential of integrated rice and catfish cultivation in Kedah and in Indonesia in terms of cropping patterns, profitability and financial feasibility, as well as specifics. This research was conducted using descriptive methods. Integrating rice and catfish cultivation in Kedah with a land area of 10,000m2 shows a negative return of -2,823.20. This is because the production value of the floating bed exceeds the cost of income. Meanwhile, in Indonesia, the integration of mina padi shows profitable or positive results because production costs tend to be smaller than floating beds. Keywords: rice cultivation, catfish farming, rice mina, siluriformes